PENGARUH INDEPENDENSI DAN EFEKTIFITAS KOMITE AUDIT TERHADAP MANAJEMEN LABA (Students' Journal of Accounting and Banking, 2013)
Abstract-The purpose of this study is to examine the effect of the independence and effectiveness of the audit committee on earning management. Independence and effectiveness of the audit committee is measured by the variable audit committee independence, financial expertise audit committee member and the meetings of the audit committee.The population of this research is 68 samples from manufacturing companies listed at Indonesian Stock Exchange during 2008 to 2011. The sampling method used in this research is purposive sampling method. The data then analyzed using multiple regression analysis. The results show that audit committee independence has positive effect and it is not significant agains earnings management, financial expertise audit committee member and the meetings of the audit committee has negative effect and it is not significant agains earnings management. Keywords: Audit Committee, Earnings Management